Comparative Study between Laparoscopic and Open Cholecystectomy: Complications and Management (Medicine Today, 2021)
Introduction: Laparoscopic cholecystectomy (LC) is currently the most widely used surgical procedure for the treatment of gallstones. The aim of the study was to analyze and compare the postoperative results of patients undergoing laparoscopic cholecystectomy or open cholecystectomy (OC) with regard to complications, recovery time and hospital stays.Materials and Methods: This is a retrospective study which was conducted at the General Hospital Khulna and some of the private Hospital in Khulna City from January 2015 to December 2019. This study which analyzed among 950 patients, 20-65 years old, diagnosed with gallstones undergoing LC or OC. We evaluated postoperative respiratory complications, surgical site infection, deep vein thrombosis, time to oral feeding and ambulation, use of antibiotics and duration of the postoperative period.Results: We analyzed 570(60%) patients undergoing LC and 380 (40%) OC. Most patients were female (55%). Patients' comorbidities were hypertension (12.8%), diabetes mellitus (4.5%) and asthma (1.00%). LC resulted in lower prevalence of postoperative complications (2.8%) than OC (3.4%). Postoperative hospitalization for 2-3 days was found in LC patients and 5-7 days in OC.Conclusion: Laparoscopic cholecystectomy showed higher benefits for patients with lower prevalence of postoperative complications, feeding earlier and shorter mean hospital stay compared with open cholecystectomy.Medicine Today 2021 Vol.33(1): 19-21